(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Genetic diversity in 38 traditional local rice genotypes grown as Jhum in the hilly areas was studied under rainfed condition through Mahalanobis D2 statistic for grain yield and yield contributing characters. The genotypes were grouped into five clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster V contained the highest number of genotypes (12) and the cluster I and III contained the lowest (5). The highest intra-cluster distance was noticed for the cluster III and lowest for cluster I. The highest inter-cluster distance was observed between cluster I and III followed by cluster II and III, cluster III and IV and the lowest between cluster II and IV. Regarding inter-cluster distance, the genotypes of cluster III showed high genetic distance from all other clusters. The genotypes from cluster III could be hybridized with the genotypes of other clusters for producing transgressive segregants. Based on positive value of vector 1 and vector 2, flag leaf length, flag leaf width, days to 50% flowering, days to maturity, unfilled grain panicle-1, grain length and grain length breath ratio had maximum contribution towards genetic divergence. The highest cluster means for plant height, filled grains panicle-1 and yield were obtained from cluster III. The highest flag leaf width, days to 50% flowering, unfilled grain panicle-1, grain length, grain breath and grain length breath ratio while the lowest mean value for yield were found in cluster I. The lowest days to 50% flowering and maturity, and highest mean value for 1000-grain weight were found in cluster IV. Therefore, more emphasis should be given on cluster I and cluster III for selecting genotypes as parents for crossing with the genotypes of cluster IV which could produce new recombinants with desired traits. DOI: http://dx.doi.org/10.3329/bjpbg.v24i2.17003